E-health, assistive technologies and applications for assisted living challenges and solutions - Röcker, Carsten 1975-; Ziefle, Martina Cornelia 1962- (Medical Information Science Reference, 2011)
Reviews existing literature in assistive technologies and provides suggestions and solutions for improving the quality of assisted living facilities and residences through the use of e-health systems and services
Includes bibliographical references
Keywords: Medical informatics; Assistive computer technology; Congregate housing; Unterstützungstechnologie; Medizinische Informatik; Aufsatzsammlung